The Role of DHEA, NGF, and ADAMTS5 Pathways in Osteoarthritis and Current Developments - Duygu Sarı Ak; Nazlı Helvacı; Ömer Alomari; Elif Bilge Yılmaz; Muhammed Munir Al-Jebaili; Alev Kural (Bagcilar Medical Bulletin, 2023)

(untitled)
Degenerative joint disease is a condition that affects joints and is commonly referred to as osteoarthritis (OA). This form of arthritis is most prevalent among women and tends to become more frequent as people age. The pathogenesis of OA involves an imbalance of cytokines in favor of pro-inflammatory cytokines. However, the steroid hormone dehydroepiandrosterone (DHEA) exerts chondroprotective effects and regulates the balance of catabolic factors such as thrombospondin motif disintegrin and metalloproteinase (ADAMTS), thereby playing a role against OA. Pro-inflammatory cytokines induce aggrecanases, such as ADAMTS5, which degrade the extracellular matrix and contribute to OA. The molecule nerve growth factor (NGF), associated with pain in OA, is important for cartilage homeostasis, and DHEA can modulate pain by interfering with NGF receptors. This review covers the roles of DHEA, ADAMTS5, and NGF in the pathogenesis of OA, their relationship with pain pathways, and their use in current treatments. We also anticipate that these pathways will be crucial in developing new strategies to prevent and treat OA, and understanding their interactions may make it possible to enhanced the quality of life of patients with OA.